Ecological Rehabilitation of Surface Mined Lands - Soni, P.; Vasistha, H. B.; Kumar, Om (Indian Forester, 1991)
In this paper various measures for reclamation of surface mined lands have been suggested to keep the ecological balance and sustainable ecosystem.